Use of Online Learning Media and Learning Behavior as Predictors of Student Accounting Understanding - Han Tantri Hardini; Mohammad Taufiq; Moh Danang Bahtiar; vivi Pratiwi (Universitas Pahlawan Tuanku Tambusai, 2021)
The Covid-19 pandemic has an impact on all fields, especially education, which requires learning to be done online. Therefore the use of online learning media and learning behavior is important to study to determine the effect on learning outcomes in the form of understanding. The purpose of this study was to determine the effect of the use of online learning media and the learning behavior students on the level of accounting understanding in the Accounting Introduction course. The sample in this study was 63 undergraduate students of Accounting Education class 2020. The data collection technique used was a questionnaire, while data analysis using multiple regression. The results: (1). The use of online learning media has an effect on the level of accounting understanding with the t-count> t-table, namely 3,345>1,67022, (2). Learning behavior affects the level of accounting understanding as evidenced by t-count> t-table, namely 2,995>1,67022 and (3). The use of online learning media and student accounting learning behavior simultaneously affects the level of accounting understanding as evidenced by the value of F-count>F-table, namely 23,179>3,15. The conclusion of this study is the use of online learning media and student learning behavior affects the level of accounting understanding.